Tactics for negotiating agreements through collaborative decision-making processes - Lynn, Jewlya, author; Colorado Institute of Public Policy, publisher (Colorado State University. Libraries, 2006)
Negotiation has been used in many natural resource dialogues, including a wide range of watershed issues. According to the legislation authorizing the Interbasin Compact Charter, a framework for negotiation is an essential component of building a lasting model for addressing water disputes in Colorado (C.R.S. 37-75-105(3)a). A negotiation framework has many different shapes, drawing not only from the most traditional negotiation literature, but also from literature on mediation, facilitation, policy dialogues, consensus processes, decision-rules, and information and fact gathering processes. Collectively, this is a body of literature that addresses the need for collaborative decision-making processes to find solutions to disputes between multiple stakeholders. It identifies tactics for participants to navigate a conflict, move from exploration to the development of proposals, and eventually reach outcomes that benefit one or all parties.
January 2006.
Keywords: Watershed management -- Colorado; Decision making -- Colorado